Racism and nationalism during and beyond the COVID-19 pandemic. Issue 5 (9th April 2021) - Elias, Amanuel; Ben, Jehonathan; Mansouri, Fethi; Paradies, Yin
ABSTRACT: Racism and xenophobia associated with the coronavirus (COVID-19) pandemic disproportionately affect migrants and minority groups worldwide. They exacerbate existing patterns of discrimination and inequity, impacting especially those already facing intersecting social, economic and health vulnerabilities. In this article, we explore the nature and extent of racism sparked by COVID-19. We briefly introduce the relationship between historical pandemics and racist sentiments and discuss ethnic and racial disparities in relation to COVID-19. We contextualize racism under COVID-19, and argue that an environment of populism, resurgent exclusionary ethno-nationalism, and retreating internationalism has been a key contributor to the flare-up in racism during the COVID-19. We then discuss links between racism, nationalism and capitalism, and consider what intercultural relations may look like in a post-outbreak world. We conclude by highlighting the potential effects of COVID-racism on intercultural relations, and the national and global implications for social policy.